USE OF PALEOMAGNETIC EVIDENCES FOR SOME TECTONIC IMPLICATIONS OF AQRA LIMESTONE OUTCROPSNORTHEASTERN IRAQ - Al-Khersan, Emad; Hijab, Basim; Baban, Ezzadin (Iraqi Journal of Science, 2024)
Maastrichtian Aqra limestone Formation at Maukaba and Zardabe localities were sampled for paleomagnetic investigations. 80 oriented limestone drill cores were collected from these localities, which are situated at the northeast part of Iraq. Following stepwise thermal demagnetization procedures, two main magnetic components were determined; a low-temperature component at (20-200)ºC that is regarded as overprint secondary unstable magnetic component with magnetic direction around the present Earth’s field; and medium - high temperature component at (250-600)ºC which is carried by high coercivity magnetic grains. It shows stable magnetic component. IRM reveals that the remanent magnetization in the Aqra limestone Formation is of a depositional origin and carried by a detrital magnetite grains. Rock magnetic analysis indicates that the primary magnetite is the dominant remanence carrying minerals observed in Maukaba and Zardabe specimens. Both of these rocks show stable and reverse paleomagnetic directions. There is a clear difference in the declinations between these two localities, which is probably due to the existed transverse faults and local tectonic movements. These movements usually indicated by the divergence of fold axis of Azmar anticline. By removing of these paleo movements It is clearly indicated that the folding and the divergence in the fold axis happened after Aqra Limestones rocks acquired their primary magnetic directions.It seems that the Neotethys Ocean to the north and northeast of studied area was still there during Maastrichtian age. The closure of this ocean apparently happened sometime between the Maastrichtian and Lower Tertiary. The rotational movement of Afro-Arabian plate towards the northeast part of Iraq causing the closing of the ocean and then the collision with Iranian and Turkish micro plates. This movement caused the Arabian plate to move about 20 degrees in latitude.